(untitled) - Van Horne, James C. (London, 1995)
This book is used in the Applied Capital Budgeting at University of Massachussetts Dartmouth. It's a very helpful and useful book. In order to understand time value of money, financial statement analysis , capital budgeting and risk , return
Keywords: Business enterprises,Corporations; Finance,Finance